1984
DOI: 10.1146/annurev.aa.22.090184.001535
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic Radio Jets

Abstract: Baade & Minkowski (3) first used the term jet in an extragalactic context, describing the train of optical knots extending ,-~ 20" from the nucleus of M87 ; the knots resemble a fluid jet breaking into droplets. They suggested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
382
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(407 citation statements)
references
References 98 publications
(155 reference statements)
24
382
1
Order By: Relevance
“…Agudo et al 2001) indicate stationary conical components in the observer frame in parsec-scale jets, which could be identified as recollimation shocks. We note that systems of repeated oblique (conical) shocks are observed in jet structures at vastly discrepant spatial resolutions, for instance in the radio galaxy NGC 6251 (Bridle & Perley 1984), interpreting this as a quasiself-similar pattern, with the local scales all proportional to radial distance along the jet. Marscher et al (2008Marscher et al ( , 2010 showed high-resolution radio images and optical polarization measurements of the BL Lac-type object PKS 1510-089, which revealed a bright feature in its jet that caused a double flare of radiation from optical frequencies to TeV gamma-ray energies as well as a delayed outburst at radio wavelengths.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 84%
“…Agudo et al 2001) indicate stationary conical components in the observer frame in parsec-scale jets, which could be identified as recollimation shocks. We note that systems of repeated oblique (conical) shocks are observed in jet structures at vastly discrepant spatial resolutions, for instance in the radio galaxy NGC 6251 (Bridle & Perley 1984), interpreting this as a quasiself-similar pattern, with the local scales all proportional to radial distance along the jet. Marscher et al (2008Marscher et al ( , 2010 showed high-resolution radio images and optical polarization measurements of the BL Lac-type object PKS 1510-089, which revealed a bright feature in its jet that caused a double flare of radiation from optical frequencies to TeV gamma-ray energies as well as a delayed outburst at radio wavelengths.…”
Section: Jets and Multiple Oblique Shocksmentioning
confidence: 84%
“…The luminosity boosting for these objects may help to make them just bright enough to be detectable above the FIRST survey flux limit. Finally, the magnetic field configurations derived from polarimetry studies (e.g., Bridle & Perley 1984) indicate that the magnetic field in FR-II radio-galaxies is predominantly aligned along the jet for most of its length, whereas FR-I objects are characterized by perpendicular and parallel components. This may suggest a correlation between the DMH mass and the efficiency in producing the magnetic field alignment required to produce brighter radio emission.…”
Section: Black Hole Properties Involved In Quasar Triggeringmentioning
confidence: 99%
“…Strong extended radio emission is indicative of powerful outflows interacting with the intracluster medium (e.g., Bridle & Perley 1984). In contrast, of the five well-fit clusters, only two (A1795 and A2199) are known to have strong extended radio sources in their centers (4C 26.42 and 3C 338, respectively).…”
Section: No 1 2003 Galaxy Clusters With Thermal Conductionmentioning
confidence: 99%